Enhancing Penetration Ability of Semiconducting Polymer Nanoparticles for Sonodynamic Therapy of Large Solid Tumor. Issue 6 (6th January 2022) - Wang, Xin; Wu, Min; Li, Haoze; Jiang, Jianli; Zhou, Sensen; Chen, Weizhi; Xie, Chen; Zhen, Xu; Jiang, Xiqun
Abstract: Sonodynamic therapy (SDT) holds growing promise in deep‐seated or large solid tumor treatment owing to its high tissue penetration depth ability; however, its therapeutic efficacy is often compromised due to the hypopermeable and hypoxic characteristics in the tumor milieu. Herein, a semiconducting polymer nanoparticle (SPNC) that synergistically enhances tumor penetration and alleviates tumor hypoxia is reported for sonodynamic therapy of large solid tumors. SPNC comprises a semiconducting polymer nanoparticle core as a sonodynamic converter coated with a poly (ethylene glycol) corona. An oxygen‐modulating enzyme, catalase, is efficiently conjugated to the surface of nanoparticles via the coupling reaction. Superior to its counterpart SPNCs (SPNC2 (84 nm) and SPNC3 (134 nm)), SPNC with the smallest size (SPNC1 (35 nm)) can efficiently penetrate throughout the tumor interstitium to alleviate whole tumor hypoxia in a large solid tumor model. Upon ultrasound (US) irradiation, SPNC1 can remotely generate sufficient singlet oxygen to eradicate tumor cells at a deep‐tissue depth. Such a single treatment of SPNC1‐medicated sonodynamic therapy effectively inhibits tumor growth in a large solid tumor mouse model. Therefore, this study provides a generalized strategy to synergistically overcome both poor penetration and hypoxia of large tumors for enhanced cancer treatment. Abstract : Semiconducting polymer nanoparticles (SPNCs) are developed for sonodynamic therapy of large solid tumors. SPNC with the smallest size (SPNC1) can efficiently penetrate throughout the tumor interstitium to alleviate the whole tumor hypoxia and generate sufficient singlet oxygen to eradicate tumor cells at a deep‐tissue depth upon ultrasound irradiation, leading to the enhanced antitumor efficacy of large solid tumor.